An Overview of Trypanosoma brucei Infections: An Intense Host–Parasite Interaction - Ponte-Sucre, Alicia (Frontiers in Microbiology, 2016)
T. brucei rhodesiense and T. brucei gambiense, the causative agents of Human African Trypanosomiasis (HAT), are transmitted by tsetse flies. Within the vector, the parasite undergoes through transformations that prepares it to infect the human host. Sequentially these developmental stages are the replicative procyclic (in which the parasite surface is covered by procyclins) and trypo-epimastigote forms, as well as the non-replicative, infective, metacyclic form that develops in the vector salivary glands. As a pre-adaptation to their life in humans, metacyclic parasites begin to express and be densely covered by the Variant Surface Glycoprotein (VSG). Once the metacyclic form invades the human host the parasite develops into the bloodstream form. Herein the VSG triggers a humoral immune response. To avoid this humoral response, and essential for survival while in the bloodstream, the parasite changes its cover periodically and sheds into the surroundings the expressed VSG, thus evading the consequences of the immune system activation. Additionally, tools comparable to quorum sensing are used by the parasite for the successful parasite transmission from human to insect. On the other hand, the human host promotes clearance of the parasite triggering innate and adaptive immune responses and stimulating cytokine and chemokine secretion. All in all, the host-parasite interaction is extremely active and leads to responses that need multiple control sites to develop appropriately.